Determinação da velocidade pico a partir de diferentes protocolos incrementais: reprodutibilidade e correlação com a performance em corridas de endurance - Peserico, Cecília Segabinazi (2012)
Peak running speed (Vpeak) has been shown to be an effective predictor of endurance running performance, and such as other physiological variables (maximal oxygen uptake and the thresholds related to blood lactate responses) is determined from maximal incremental tests. Furthermore, the design of the incremental protocol influences the responses of these variables. Thus, the objective of the present study was to verify the best protocol, from incremental tests with different rates of increment (0.5 km·h-1, 1 km·h-1 e 2 km·h-1), for determining Vpeak. Twenty runners participated aged 25.3 ± 3.1 years, body mass 76.2 ± 8.5 kg, height 178.5 ± 0.1 cm, body mass index 23.9 ± 2.3 kg·m-2, body fat 13.5 ± 3.2%, and experience in competing 10 km (practice time of 3.5 ± 3.2 years). Participants performed, randomly, in test-retest, three maximal running incremental testes on a motorized treadmill with an initial velocity of 8 km·h-1 and 3-min stages durations. Each test differed from the rate of increment between stages, which are 0.5 km·h-1 (slight protocol), 1 km·h-1 (intermediate protocol) and 2 km·h-1 (heavy protocol). After the incremental tests, participants performed two running performances in one hour time trial, in which the first was performed on a treadmill and the second in 400m athletics track. During the tests at the end of each stage, heart rate (HR) and rating of perceived exertion (RPE) were monitored, and the highest values of HR and RPE reached at the end of the maximal incremental test considered maximal heart rate (HRmax) and maximal rating of perceived exertion (RPEmax). The Vpeak was considered the maximum speed attained in the incremental test, being adjusted from the equation proposed by Kuipers et al. (2003), if the participant didn't complete the last stage of the test. During the performances mean speed (race pace) were recorded every 15 minutes; the values of HR and RPE were recorded every 10 minutes to determine HRmax, mean heart rate (HRmean) and RPEmax. At the fifth minute after tests (incremental tests and performances) blood samples were collected for the determination of the peak blood lactate concentration (LApeak).The reproducibility test-retest was represented by intraclass correlation coefficient (ICC), Pearson's correlation coefficient (r), standard error of measurement (SEM), coefficient of variation (CV) and Bland and Altman analysis. The variables obtained in the three different incremental protocols were compared using a repeated measures ANOVA; performances were compared by Student's t test to related samples. The relationships between performances and Vpeak were demonstrated by Pearson correlation coefficient (r), standard error of estimate (SEE) and by simple linear regression analysis. For all analysis significance level of P < 0.05 was adopted. The results showed that the values of Vpeak were statistically different between slight, intermediate and heavy protocols (14.6 ± 0.7 km·h-1; 15.6 ± 0.7 km·h-1; 16.5 ± 0.8 km·h-1, respectively). Further, the Vpeak showed high reproducibility in all three iv protocols, with high correlation values (r = 0.85 to 0.96; ICC = 0.85 a 0.94) and low values of SEM (0.17 to 0.30) and CV (1.13% to 1.78%). The variables test duration, HRmax and PSEmax also presented as reproducible; however, the LApeak post-exercise was not reproducible, mainly due to high CV values and low values of ICC. The Vpeak determined in the intermediate protocol presented the highest correlation (r = 0.88 and 0.83, treadmill and track, respectively) and lowest SEE (treadmill = 0.38; track = 0.47) with both performances. The mean speed of the one hour time trial performed on the treadmill (11.8 ± 0.8 km·h-1) was lower than in the track performance (12.2 ± 0.8 km·h-1). In conclusion, the rate of increment used in incremental protocol influenced the responses of Vpeak and other physiological varibles (HRmax, LApeak post-exercise, submaximal HR and RPE). Furthermore, Vpeak showed high reproducibility and correlation with running performance in one hour time trial.